2000
DOI: 10.1159/000054530
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Serotonin Receptor Subtypes On Growth Hormone Secretion

Abstract: The role of serotonin (5-HT) in the regulation of growth hormone (GH) secretion remains unclear due to the existence of many different receptors that mediate the 5-HT actions, and the lack of suitable specific agonist and antagonist drugs. In the present work we have taken advantage of the recent development of new selective 5-HT drugs in order to clarify the role played by different 5-HT receptor types and subtypes on GH secretion. The experiments were carried out on beagle dogs. GH-releasing hormone (GHRH) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…bolus at 0 min) at a dose (100 µg) which markedly increases GH secretion in dogs, as previously reported [19, 20]. …”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…bolus at 0 min) at a dose (100 µg) which markedly increases GH secretion in dogs, as previously reported [19, 20]. …”
Section: Methodssupporting
confidence: 78%
“…bolus at 0 min, Peninsula Laboratories, Merseyside, UK) administered at a dose of 90 µg (based on previous reports by our group in dogs) [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the stimulatory effect of serotonin on GH secretion is limited to specific periods of development. The serotoninergic 5-HT 1 and 5-HT 2 receptor subtypes have been shown to be involved as stimulatory elements in the control of GH in dogs (37) and in humans (38), whereas GH secretion seems to be independent of the degree of activation of 5-HT 3 receptors (37). In neonatal rats, it has been proposed that changes in serotoninergic activity at 5-HT 2 receptors mediates the inhibition of GH secretion in maternal separation (31).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies showed a positive effect of brain serotonin on the secretion of adrenocorticotropic hormone (Jørgensen, 2007). The stimulating effect of the brain serotonergic system on growth hormone secretion can be initiated by either growth hormone-releasing hormone release from the arcuate nucleus (Vijayan et al, 1978;Murakami et al, 1986; or the suppression of somatostatin release from the paraventricular nucleus (Mota et al, 1995;Valverde et al, 2000). A majority of data indicate a complex mechanism of the serotoninregulated thyroid-stimulating hormone (TSH) secretion which may occur at the level of the hypothalamus (inhibition of thyrotropinreleasing hormone release or somatostatin secretion) or pituitary gland (stimulation of TSH secretion) (Abrahamson et al, 1987;Toivonen et al, 1990;Masalova and Sapronov, 2009).…”
Section: Introductionmentioning
confidence: 99%